The Brazilian version of the Hip Sports Activity Scale: translation and cross-cultural adaptation - Mathias, Letícia Nunes Carreras Del Castillo; Cardinot, Themis Moura; Sá-Caputo, Danúbia da Cunha de; Moura-Fernandes, Márcia Cristina; Bernardo-Filho, Mário Bernardo-Filho; Soares, Gustavo Leporace de Oliveira Lomelino; Batista, Luiz Alberto; Oliveira, Liszt Palmeira de (São Paulo Medical Journal, 2022)
BACKGROUND: The Hip Sports Activity Scale (HSAS) is a reliable and valid tool for determining the levels of sports activities among patients with femoroacetabular impingement (FAI). OBJECTIVE: To translate and cross-culturally adapt the HSAS to the Brazilian Portuguese language. DESIGN AND SETTING: This was a cross-sectional study conducted at the State University of Rio de Janeiro. METHODS: The Brazilian version of the HSAS was developed following a process that comprised six steps: translation, synthesis, back-translation, review by committee, pretesting and submission of documentation to the developers. The translation phase involved three independent bilingual translators whose mother language was Brazilian Portuguese. The back-translation phase involved three ndependent translators whose mother language was English. In order to verify comprehension of the questionnaire, 30 undergraduate students in physical education (65% men), with mean age 23.2 years (standard deviation = 6.8), participated in the pre-testing phase. RESULTS: During the translation step, some terms and expressions were changed to obtain cultural equivalence to the original HSAS. In the pre-testing phase, each item of the scale showed a comprehension level of 100%. CONCLUSION: The HSAS was translated from English to the Brazilian Portuguese language and adapted to Brazilian culture. The HSAS validation is ongoing.